2002
DOI: 10.1646/0006-3606(2002)034[0297:dbcasd]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dung Beetle Communities and Seed Dispersal in Primary Forest and Disturbed Land in Amazonia1

Abstract: Seeds from tropical fiuiting trees ingested and defecated on the soil surface by primary dispersers (such as primates) are vulnerable to destruction from rodents, insects, and Fungi. Burial by dung beetles as an incidental result of their feeding and nesting activities often provides these seeds with rehgia from attack. To examine the effect of habitat disturbance on the dung beetle communities involved in this process, I surveyed dung beetles at three sites in the Amazon basin, in the states of Par& Amazonas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
1
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 44 publications
4
85
1
13
Order By: Relevance
“…Nevertheless, the density of five (out of six) most abundant species decreased with land-use intensity, whereas only one species showed a higher abundance in young secondary forest and agroforest compared to the natural forest. Similarly, in Amazonia most but not all dung beetles were negatively affected by habitat disturbance (Vulinec 2002). Furthermore, Roslin and Koivunen (2001) found that different species show very dissimilar responses to changes in landscape structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the density of five (out of six) most abundant species decreased with land-use intensity, whereas only one species showed a higher abundance in young secondary forest and agroforest compared to the natural forest. Similarly, in Amazonia most but not all dung beetles were negatively affected by habitat disturbance (Vulinec 2002). Furthermore, Roslin and Koivunen (2001) found that different species show very dissimilar responses to changes in landscape structure.…”
Section: Discussionmentioning
confidence: 99%
“…Diversity of some groups, such as solitary bees and wasps, may even increase with land-use intensity (Klein et al 2002) and Bornean hawkmoths (Lepidoptera, Sphingidae) do not reflect the influence of habitat disturbance (e.g., Schulze and Fiedler in press). The diversity of carrion beetles may not be seriously affected by forest clearance and the establishment of plantations (Hanski 1989), although reduced abundance and diversity in clear cuts may occur (Vulinec 2002). Klein (1989) and Andresen (2002a) quantified the reduced diversity of decomposer organisms as a result of forest fragmentation (see also Didham et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being recognized as important decomposer organisms (involved with nutrient recycling) (Hanski and Krikken 1991), their ecological role as a secondary seed disperser has recently received increasing attention (Estrada and Coates-Estrada 1991;Vullnec 2002). It has been reported worldwide that the species diversity of dung beetles has been rapidly decreasing with fragmentation and isolation of their habitats arising directly or indirectly because of increasing human activity (Klein 1989;Davis et al 2001;Halffter and Arellano 2002;Feer and Hingrat 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Scarabaeinae have also been widely used as indicator groups (see Nichols et al 2007, including a meta-analysis and a synthesis of 33 publications; Howden and Nealis 1975;Klein 1989;Halffter et al 1992;Estrada et al 1998;Davis et al 2000;Vulinec 2000Vulinec , 2002Andresen 2003;Scheffler 2005;Quintero and Roslin 2005;Shahabuddin et al 2005;Chapman et al 2003;Avendaño-Mendoza et al 2005;Vulinec et al 2006, along with some other references included in our 'Introduction and discussion').…”
Section: Introductionmentioning
confidence: 99%